Gobal and Local: Worship Music and the 'Logophonic' Principle, or Lessons from the Songhai. (October 2019) - Devalve, John R
The Christian church has always lived in tension between its global and its local identities, between gospel and culture. One aspect in which this tension plays out is in worship music. As the gospel came to them, many African churches adopted a North American/European form of song, ignoring or neglecting their local, traditional music. They opted for a more global identity and minimized their local identity. The church amongst the Songhai of West Africa is an example of this phenomenon. A church that neglects its local identity, however, has little appeal to the surrounding society and loses its prophetic voice to the community. Resolving the tension between the two identities is an important matter for every church. Thinking through worship music practices plays a key part in resolving this tension. A tool called the 'logophonic' principle may be of help in this regard. The tool looks at both words (lyrics) and sounds (accompaniment) to reexamine and renew worship practices and craft new music for congregations. This article explains how this tool might work and urges the necessity of good theological thinking and about worship and worship music.